C-Reactive protein reactions to glucose-insulin-potassium infusion and relations to infarct size in patients with acute coronary syndromes. Issue 1 (December 2015) - Alkofide, Hadeel; Huggins, Gordon; Beshansky, Joni; Ruthazer, Robin; Peter, Inga; Ray, Madhab; Mukherjee, Jayanta; Selker, Harry
Abstract Background Some benefits of glucose-insulin-potassium (GIK) in patients with acute coronary syndromes (ACS) may be from an anti-inflammatory effect. The primary aim of this study was to assess the impact of GIK administration early in the course of ACS on inflammatory marker C-reactive protein (CRP) levels. A secondary aim was to investigate the association between CRP and 30-day infarct size. Methods and Results Retrospective analysis of participants with ACS randomly assigned to GIK or placebo for at least 8 h in the IMMEDIATE Trial biological mechanism cohort (n = 143). High sensitivity CRP (hs-CRP) was measured at emergency department presentation, and 6 and 12 h into infusion. Logarithmically transformed hs-CRP values at 12-hours were lower with GIK vs. placebo (mean =0.65 mg/L in GIK, 0.84 mg/L in placebo), with a marginal trend toward significance (P = 0.053). Furthermore, using mixed models of hs-CRP, time, and study group, there was a significant increase in hs-CRP levels over time, but the rate of change did not differ between treatment arms (P = 0.3). Multivariable analysis showed that an elevation in hs-CRP, measured at 12 h, was an independent predictor of 30-day infarct size (β coefficient, 6.80;P = 0.04) using sestamibi SPECT imaging. Conclusions The results of this study show no significant effect of GIK on hs-CRP. In addition our results show that in patients with ACS, hs-CRP measured as early as 12 h can predict 30-day infarct size.